In Vitro Induction Of Tetraploid Pummelo âNambanganâ (Citrus maxima (Burm.) Merr.) By Colchicine Treatment Using Germinated Seed, Shoot Tip And Cotyledonary Node As Explants - Wulandari, Dyah Retno; Purwito, Agus; Susanto, Slamet; Husni, Ali; Ermayanti, Tri Muji (ANNALES BOGORIENSES, 2015)
Tetraploid citrus are important for interploidal hybridization to create triploid seedless citrus.Â  Colchicine is the most commonly used as antimitotic agent to induce polyploid plants.Â  Tetraploid induction by colchicine in Pummelo âNambanganâ was conducted in vitro using different types of explants.Â  The aim of this research was to induce tetraploid pummelo âNambanganâ by colchicine treatment using germinated seed, shoot tip and cotyledonary node as explants.Â  Tetraploid shoot induction was conducted by soaking germinated seeds, shoot tips and cotyledonary nodes in 0.1% colchicine for 1, 3 and 5 h.Â  Regenerant shoots were grown on MS medium and their growth was observed after four weeks in culture.Â  Ploidy level was determined using flow cytometry analysis.Â  Stomata density, length and width of stomatal guard cell were also recorded. The results showed that shoot elongation was inhibited by colchicine treatment.Â  Soaking of shoot tip explants in 0.1% colchicine for 1 h resulted in 66.66% of putative tetraploid shoots.Â  Compared to diploid shoots, tetraploids had lower stomata density but bigger in guard cell size.Â Keywords: colchicine, tetraploid, pummelo (Citrus maxima (Burm.) Merr.), flow cytometry, stomata,